The role of aldosterone in the development of atrial fibrillation: modern understanding of problem - N. T. Vatutin; A. N. Shevelok; I. N. Kravchenko (SINAPS LLC, 2019)
The review of literature presents modern ideas about the role of aldosterone in the development and maintenance of atrial fibrillation. It is shown that hormone takes part in all stages of the electrophysiological and structural atrial remodeling, contributing to the formation of the arrhythmia substrate. It was noted that adverse effects of the aldosterone in the myocardium are realized not only due to its high systemic production but also because of its direct synthesis in the atrial tissues. Increased expression of mineralocorticoid receptors in cardiomyocytes also play important role in the development of atrial fibrillation. It is demonstrated that hyperaldosteronemia can be a cause as well as effect of atrial fibrillation. The episode of arrhythmia is characterized by neurohormonal activation, increased intramyocardial aldosterone synthesis and high mineralocorticoid receptors expression. This contributes to the further progression of atrial remodeling and makes conditions for the arrhythmia recurrences.